Diminished DNA binding affinity of DMRT1 caused by heterozygous DM domain mutations is a cause of male infertility - Marić, Tihana; Castillo-Madeen, Helen; Klarić, Monika Logara; Barišić, Antun; Trgovec-Greif, Lovro; Murphy, Mark W; Juchnewitsch, Anna-Grete; Lillepea, Kristiina; Dutta, Avirup; Žunić, Lucija; Stendahl, Alexandra M; Punab, Margus; et al. (Human molecular genetics, 2025)
The most severe form of male infertility is idiopathic non-obstructive azoospermia (NOA), a complete sperm absence in the ejaculate. We performed exome sequencing in the Croatian infertile brothers with NOA and found a variant in DMRT1 (Doublesex and mab-3 related transcription factor 1) gene that was further assessed by the EMSA assay and molecular dynamic simulations. We additionally screened for DMRT1 mutations in 1940 infertile men diagnosed with spermatogenic failure, 644 normozoospermic controls, and 105 females with primary ovarian insufficiency (POI) recruited to the GEnetics of Male INfertility Initiative (GEMINI) or Estonian Andrology (ESTAND) cohorts. DMRT1 p.Pro74Leu (chr9:g.842059C > T) variant was detected in infertile brothers in the highly conserved position within the DNA binding DM domain of the protein. EMSA assay showed reduced DNA binding of DMRT1P74L and molecular dynamic simulations showed differences in structural and dynamical properties between the wild type protein and DMRT1P74L. Plausible disease-causing DMRT1 variants were only identified in infertile men (13/1940; 0.67%), and none in 639 fertile controls. Burden testing showed an excess of rare deleterious DM domain mutations in the infertility cohort compared to gnomAD v.4.0 population-based controls (Fisher's exact test, p = 1.44 x 10-5). Three rare deleterious variants in DMRT1 were found in 104 cases of POI. The findings of this study strengthen the evidence of DMRT1 variants being a causal factor for male infertility and provide the distribution of likely pathogenic variants across the gene. This is also the first study to suggest that DMRT1 variants may also be linked to POI.